Hirntumoren im Kindes- und Jugendalter = Brain tumors in childhood and adolescence - Juhnke, Björn-Ole; Witt, Hendrik (Der Onkologe, 2016)
BackgroundIn recent years, new insights into many disciplines of pediatric neuro-oncology have been generated. These include important progress in understanding the biology of medulloblastoma, pontine glioma, low and high-grade glioma, ependymoma, embryonal tumor with multilayered rosettes (ETMR) and atypical teratoid/rhabdoid tumor (AT/RT). This ushered in a new era of clinical and molecular diagnostics and therapy.MethodsThis study is based on the research results of the German treatment network HIT as well as a selective literature review of studies published over the last 40 years.ResultsModern therapy concepts are gradually becoming integrated into clinical treatment recommendations based on the expanded understanding of tumor biology. Current therapeutic approaches are modified according to the clinical and biological risk in order to reduce the long-term toxicity in patients with a good prognosis and to improve the poor cure rates in high-risk groups. Novel imaging techniques, such as the availability of intraoperative magnetic resonance imaging (MRI) have facilitated neurosurgery. Improvements in radiotherapy planning and the increasing availability of proton beam therapy raise hopes for a long-term decrease in morbidity after irradiation. A better understanding of the pathophysiology of damage to the developing brain and other treatment-related complications are increasingly becoming the focus of research, with the aim of mitigating damage and providing children with coping mechanisms.ConclusionsThe validation and further development of the biological and clinical aspects described are required in future prospective studies within the HIT treatment network.
Gesehen am 23.08.2017